ANALISIS KERENTANAN AIRTANAH TERHADAP PENCEMARAN DI DATARAN ALLUVIAL KOTA SEMARANG MENGGUNAKAN METODE GOD DENGAN MEMANFAATKAN DATA RESISTIVITAS DAN DATA HIDROGEOLOGI - Dhana Hastuti; Tony Yulianto; Thomas Triadi Putranto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Groundwater is the water resources necessary for living things and the most desirable human. Groundwater needs to increase as the population increase. One example is in the Alluvial Plain of Semarang. To supply water necessary, the population use a tap of aquifer shallow wells. Shallow aquifer vulnerable to contamination due to the effect of shallow depth and human activities. Therefore there is a needed to conduct for research on the groundwater vulnerability due to contamination. GOD is the system to determine of value groundwater vulnerability due to contamination. The parameters used are the type of aquifer (G), type of lithology aquitard (O), and the depth to groundwater table (D). These three parameters derived from resistivity data and hydrogeology data. The results of the analysis by this method has three levels of vulnerability of groundwater due to contamination the area of the vulnerability of low, moderate, and high. So it is recommended that the analysis can be made of the green open area to reduce contamination and groundwater catchment area is formed, and restrict the activities to achieve economic gains and reduce the danger of environmental contamination.